The ambient air and noise quality in India during diwali festival: A Review - Verma, Chirag; Deshmukh, Dhananjay K (Recent Research in Science and Technology, 2014)
This study deals with the effects of fireworks on the air quality over the major cities of India during the festival of light known as “Diwali”. The effects of firecrackers during the festival was assessed from the ambient concentrations of various air pollutants such as sulphur dioxide (SO2), nitrogen dioxide (NO2) and particulate matter (PM) with diameter less than 10 µm. The concentrations of gaseous pollutants such as SO2 and NO2 as well as particulate pollutants such as PM10 and PM2.5 was found about 2-6 times higher during the day of festival because of the use of huge quantity of firecrackers that emits a large amount of pollutants into the atmosphere. Previous studies indicated that the concentrations of above air pollutants during Diwali festival was found several folds higher as compared to the 24-h standard of National Ambient Air Quality Standards of India (NAAQS) given by the Central Pollution Control Board (CPCB), India. Concentrations of metallic elements analysed in fireworks aerosol samples in previous studies in India reported its higher contribution during Diwali festival as compared to the limit value of NAAQS of India. The noise levels in the Indian cities during the night of Diwali festival were also found to be higher. The deterioration of ambient air quality due to the anthropogenic activity such as the use of firecrackers in the megacities of India has significant impacts on human health on a regional scale. This review suggested the development of serious strategies to control the use of firecrackers during the festival of light in the major cities of India to protect human health.